2008
DOI: 10.1128/jvi.01910-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Cytomegalovirus gH/gL/UL128-131 Complex That Mediates Entry into Epithelial and Endothelial Cells

Abstract: The entry of human cytomegalovirus (HCMV) into biologically relevant epithelial and endothelial cells involves endocytosis followed by low-pH-dependent fusion. This entry pathway is facilitated by the HCMV UL128, UL130, and UL131 proteins, which form one or more complexes with the virion envelope glycoprotein gH/gL. gH/gL/UL128-131 complexes appear to be distinct from the gH/gL/gO complex, which likely facilitates entry into fibroblasts. In order to better understand the assembly and protein-protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
330
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(346 citation statements)
references
References 64 publications
16
330
0
Order By: Relevance
“…[6]) and then the pentameric complex in 2008 (Ryckman et al [10]) were found to be indispensable for virus and viral product transfer from endothelial cells to leukocytes (from Revello and Gerna [148]). …”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
See 1 more Smart Citation
“…[6]) and then the pentameric complex in 2008 (Ryckman et al [10]) were found to be indispensable for virus and viral product transfer from endothelial cells to leukocytes (from Revello and Gerna [148]). …”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
“…A significant contribution to the development of a HCMV vaccine was the identification of the pentameric complex (PC), which consists of HCMV gH, gL, pUL128, pUL130 and pUL131 [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the neutralizing antibody response was determined in parallel by inoculating virus-serum mixtures onto ARPE-19 epithelial cells and HELF cells. The double neutralization assay was based on the recent discovery that HCMV requires the pentamer to infect epithelial/endothelial/dendritic cells Ryckman et al, 2008), while infection of HELF cells requires the presence of gH/gL/gO on the HCMV envelope (Zhou et al, 2013). It has been demonstrated and repeatedly confirmed that neutralizing titres determined in epithelial cells are far higher than those obtained in HELF cells (Cui et al, 2008;Gerna et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The IgG antibody responses to the glycoprotein complexes representing the pentamer (gH/gL/ pUL128L), the dimer gH/gL (Hahn et al, 2004;Ryckman et al, 2008) and gB were investigated. In addition, the neutralizing antibody response was determined in parallel by inoculating virus-serum mixtures onto ARPE-19 epithelial cells and HELF cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation